Clinical-epidemiologic and serologic characteristics of Lyme disease in the Zaporizhzhia region (a retrospective analysis for 2015–2019 according to the Municipal Institution “Regional Infectious Hospital” of Zaporizhzhia Regional Council) - O. O. Furyk; K. A. Pak; O. V. Riabokon; D. A. Zadyraka; Yu. Yu. Riabokon (Zaporožskij Medicinskij Žurnal)
The aim of the work is to clarify the clinical and laboratory features of Lyme disease in the Zaporizhzhia region on the basis of a retrospective clinical, epidemiological and serological analysis of this disease cases in the period from 2015 to 2019.